2015
DOI: 10.1177/1474515114564929
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acceptance of illness on the quality of life in patients with chronic heart failure

Abstract: The extent a patient accepts their chronic heart failure diagnosis has been shown to impact on their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 23 publications
5
52
1
1
Order By: Relevance
“…Moreover, improved knowledge of HT may affect patients’ acceptance of illness and their beliefs related to the illness and its treatment 2,29. However, few studies25 exist to confirm the correlation between acceptance of illness and adherence to pharmaceutical treatment,16 and the available articles mainly focus on AIS in the context of quality of life in chronic illness 3032…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, improved knowledge of HT may affect patients’ acceptance of illness and their beliefs related to the illness and its treatment 2,29. However, few studies25 exist to confirm the correlation between acceptance of illness and adherence to pharmaceutical treatment,16 and the available articles mainly focus on AIS in the context of quality of life in chronic illness 3032…”
Section: Discussionmentioning
confidence: 99%
“…Several reports previously showed that individual coping was substantially influenced by self‐management (Klein, Turvey, & Pies, ; Riegel & Carlson, ). Indeed, a high level of acceptance of illness resulted in better medication compliance and self‐management (Obiegło, Uchmanowicz, Wleklik, Jankowska‐Polańska, & Kuśmierz, ). Besides, the active coping strategies are more likely to facilitate self‐management and the decision‐making process that determine the actions aimed at maintaining a stable health.…”
Section: Discussionmentioning
confidence: 99%
“…| 3331 Ku smierz, 2015). Besides, the active coping strategies are more likely to facilitate self-management and the decision-making process that determine the actions aimed at maintaining a stable health.…”
Section: Self-management and Coping Strategymentioning
confidence: 99%
“…Acceptance originated as a concept in psychology and has since been operationalized in healthcare to enhance the quality of life in patients due to its therapeutic implications. In adults with chronic illness, acceptance of illness has been associated with better disease management and improved quality of life, while lack of acceptance has been associated with negative outcomes, such as treatment nonadherence and psychological distress . The benefits of acceptance have also been showcased from applications in various healthcare interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with chronic illness are doubly disadvantaged, being more likely to exhibit symptoms of depression and anxiety when compared to healthy peers . As illness acceptance is often associated with positive psychosocial outcomes, helping adolescents come to accept their illness may be an important step towards alleviating these issues. Among adolescents, chronic illness currently accounts for over a quarter of all disability‐adjusted life years across countries where chronic illness is a predominant public health issue .…”
Section: Introductionmentioning
confidence: 99%